2009
DOI: 10.1088/0031-8949/80/04/045901
|View full text |Cite
|
Sign up to set email alerts
|

A tomographic description for classical and quantum cosmological perturbations

Abstract: Classical and quantum perturbations can be described in terms of marginal distribution functions in the framework of tomographic cosmology. In particular, the so called Radon transformation and the mode-parametric quantum oscillator description can give rise to links between quantum and classical regimes. The approach results a natural scheme to discuss the transition from the quantum to the classical perturbations and then it could be a workable scheme to connect primordial fluctuations with the today observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…204 and 205) They describe equally well quantum and classical states. For this reason, tomograms are suitable for a good description of the quantum-to-classical transition of the Universe, and eventually can be defined phenomenologically by cosmological observations, leading to a reconstruction of the early Universe [206][207][208][209][210][211][212] with obvious relations with its dark components in matter and in energy.…”
Section: Tomographic Description Of Quantum and Classical States Of The Universementioning
confidence: 99%
“…204 and 205) They describe equally well quantum and classical states. For this reason, tomograms are suitable for a good description of the quantum-to-classical transition of the Universe, and eventually can be defined phenomenologically by cosmological observations, leading to a reconstruction of the early Universe [206][207][208][209][210][211][212] with obvious relations with its dark components in matter and in energy.…”
Section: Tomographic Description Of Quantum and Classical States Of The Universementioning
confidence: 99%
“…The quantities in (34) and ( 35) correspond to a conserved total energy-momentum tensor. However, we may consider the energy corresponding to this to be made up of constituents, that may or may not be separately conserved.…”
Section: A New Scalar Fieldmentioning
confidence: 99%
“…However, it may be noted that here we have only one state for the universe and even the definition of probability in this context is quite vague. In another interesting approach, it was observed that if tomographic probability representations are related to extra symmetries such as Noether symmetries, they allow oscillatory behaviour of the wave function and then give rise to classical solutions which correspond to observable universes [33,34]. This approach is worked out also for general classes of extended theories of gravity.…”
Section: Classical-quantum Correspondencementioning
confidence: 99%
“…By quantum tomography one can be able to determine the state(s) prior to the measurements. Quantum tomography has applications in quantum optics, quantum information and quantum mechanics, our aim is to extend it to quantum cosmology program [7][8][9]12 . Quantum tomography measures the probability distribution for the rotated quadrature phase x θ = (a † exp(iθ) + a exp −iθ )/2 at different values of θ.…”
Section: Quantum Tomographymentioning
confidence: 99%